Edukasi Dan Pemanfaatan Tanaman Obat Untuk Kesehatan Masyarakat Rw 05 Dan Rw 06 Desa Cibiru Hilir, Kecamatan Cileunyi, Kabupaten Bandung Pada Bulan November Tahun 2021 - Kharina Septi Lestari; Nur Rakhmanto Heryana; Antri Ariani; Anggi Jamiyanti; Aris Suhardiman; Amelia Kandisa (Jurnal Abdi Masyarakat Kita, 2022)
There are many medicinal plants that have the potential to be developed as raw materials for herbal medicines but in fact have not been managed and utilized optimally by the community. There are several problems with conventional medicine, including side effects, high drug resistance, and higher prices, which have created a prolonged economic situation that has hit Indonesia. One solution that can be done in maintaining health conditions is using family medicinal plants. The purpose of family medicinal plants is that they can be used as an alternative to conventional medicine that is easy to find, no money to buy and without the need to come to a health facility. The implementation of education and utilization of family medicinal plants was carried out in RW 05 and RW 06, Cibiru Hilir Village, Cileunyi District, Bandung Regency. The number of participants in this activity involved 60 people (men and women) with an age range of 20 to 50 years, consisting of 30 people from RW 05 and 30 people from RW 06. The methods used in this activity were conducting pre-tests, counseling activities, post test, and delivery of medicinal plant seeds to residents. After the educational activities on the use of medicinal plants took place, public knowledge about family medicinal plants increased as seen from the results of the pre-test and post-test.